Tanggung Jawab Hukum Atas Produk Cacat Tersembunyi Penjualan Online Pada Marketplace Shopee - Sheilva Syahputri Assagaf; Sarah Selfina Kuahaty; Marselo Valentino Giovani Pariela (PATTIMURA Law Study Review, 2026)
Online buying and selling transactions have a higher risk than conventional buying and selling transactions. The risk of loss due to goods not arriving even though the shipping status has been completed or consumers who do not receive a refund to the wrong order number are examples of weaknesses in the online buying and selling transaction system. Another example that is most often encountered is hidden defective goods. This is because in online buying and selling, buyers cannot physically touch the goods purchased. Certainly, these incidents directly interfere with or injure consumer rights, especially the right to obtain accurate, clear information about the products offered. The purpose of this writing is to find out and explain the legal responsibility of traders for hidden defective products in the Shopee marketplace and to find out and explain the compensation given to consumers in the Shopee marketplace. The research method used is a normative legal research type. The problem approach used is the statutory approach and the conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The procedure for collecting legal materials through literature studies, which will be linked to legal facts and legal consequences so that they will be analyzed based on qualitative methods. The results of the study indicate that the seller's responsibility for hidden defective products is included in contractual liability. Civil liability based on agreements/contracts from companies and business actors (both goods/services) for losses experienced by consumers. While the compensation in question is in the form of a refund or replacement of goods and/or services of the same type or equivalent value, or health care and/or provision of compensation in accordance with the provisions of applicable laws and regulations. Compensation is carried out within a period of 7 days after the transaction date. Furthermore, consumers as regulated in the UUPK have the right to receive compensation, damages and/or replacement, if the goods and/or services received do not comply with the agreement or are not as they should be.